THE EFFECTIVENESS OF USING STAD MODEL TO IMPROVE STUDENTS’ WRITING ABILITY OF EXPOSITION TEXT - Nursepti Anggraeni; Aa Qonaatun; Ina Rahiyatussakinah (CV. Bunda Ratu, 2025)
This research aims to determine the significant difference score of using STAD model to improve students writing ability of exposition text and to describe the students writing ability after using STAD model. This research used quasi-experimental design with a pre-test and post-test approach. This research subjects consisted of 11th grade students at Daar Al Ilmi Islamic Boarding School with divided into two groups: 11 IPA 2 as experimental consisting 29 students used STAD model and 11 IPS 2 as control consisting 22 students used conventional model. Data were collected through writing test design to measure students ability before and after treatment. Data analysis was conducted using t-test. The results showed that there is significant different score to improvement students writing ability between two groups. The mean post-test score in the control class was 77.82, while in the experimental class it was 80.55. Data analysis showed a significance value (t-test) of 0.002 ≤ 0.05, these results show that H0 is rejected and Ha is accepted, which indicates a significant difference between the two groups. Thus, it can concluded that STAD model has been proven to be effective in the writing ability. The use of this model not only improve writing ability, but also active in discussing with their friends, can increase their enthusiasm and interest in the learning process. Keywords: cooperative learning, exposition text, STAD, writing